CYTOTOXICITY AND GENOTOXICITY OF ENDODONTIC IRRIGANTS ON HUMAN CELLS - Longo, João Paulo Figueiró; Valois, Caroline Alves; Tapajós, Érica Correio Coelho; Santos, Maria de Fátima Menezes Almeida; Azevedo, Ricardo Bentes de (Archives of Oral Research, 2010)
OBJECTIVE: Endodontic irrigants solutions with antibacterial activity have been used in treatment of teeth with infected root canals; however, these solutions can irritate periapical tissues. The aim of this study was to evaluate the cytotoxity and genotoxicity of different endodontic irrigants solutions – sodium hypochlorite (1% and 2%), calcium hydroxide (0.2%), and HCT20 in human KB cells. MATERIAL AND METHOD: Cells were incubated with solutions for 2 and 24 hours. The cell viability was assessed after the trypan blue exclusion and the frequency of cell death mechanism (apoptotic or necrotic) was determined by acridine orange/ethidium bromide fluorescent dyeing test. The genotoxicity effects were assessed by the micronucleus assays. RESULTS AND DISCUSSION: The results showed that Ca(OH)2 alone or in combination with tergentol (HCT20), and NaOCl induced cytotoxicity in KB causing death cells by apoptosis. The micronuclei test showed that KB treated with NaOCl (1%) present an increase in the frequency of micronucleus compared to the control group.